1995
DOI: 10.1080/09540129550126849
|View full text |Cite
|
Sign up to set email alerts
|

Caring for people with AIDS in a Nigerian Teaching Hospital: Staff attitudes and knowledge

Abstract: Health workers (HWs) play a pivotal role in preventative programmes being implemented to combat the steady increase in the prevalence of HIV infection and AIDS in Nigeria. We report on a questionnaire survey conducted in October, 1993 among 111 doctors, 92 nurses and 53 non-health workers at the University of Ilorin Teaching Hospital, Ilorin, Nigeria. The aim was to assess their knowledge of AIDS (for all groups) and the attitude of the HWs only towards the care of patients with AIDS (PWAs). Although important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
47
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 2 publications
7
47
1
Order By: Relevance
“…These findings are similar to those in other Nigerian studies (Adelekan et al, 1995;Oyeyemi et al, 2006).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…These findings are similar to those in other Nigerian studies (Adelekan et al, 1995;Oyeyemi et al, 2006).…”
Section: Discussionsupporting
confidence: 83%
“…This suggests that the discriminatory attitudes exhibited by the respondents are of multifactorial aetiology and not confined to any group of HCWs. However, the tendency of nurses and auxiliary nurses to be more discriminatory, which has previously been reported (Adelekan et al, 1995), may be due to their poorer knowledge of HIV transmission in comparison to physicians, as has been shown in previous studies (Adelekan et al, 1995;Ezedinachi et al, 2002). The importance of this finding is that in the current roll-out programmes a lot more HIV care is provided through nurses than doctors.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…In the current study there were 93.4% who have never attended any occupational training program regarding AIDS or HIV prevention. The findings compare favourably with those reported from other research (Adelekan et al, 1995;Ugochukwu ,2003;Lui et al .,2012 ) . They had also found that important knowledge gaps and appreciation of occupational training programs in all health categories which they considered.…”
Section: Resultssupporting
confidence: 80%
“…12,13 Knowledge were often inadequate, while perceptions and misconceptions were prevalent as were prejudices and popular myths in the societies concerned about people with AIDS especially among young people. [14][15][16][17][18][19] The exceptions are in situations where Sex/AIDS education are entrenched in the school curriculum. 20,21 In 1981, the Nigerian Educational Research and Development Council (NERDC) developed and incorporated a school based population education programme at the secondary school level.…”
Section: Introductionmentioning
confidence: 99%